2021
DOI: 10.1177/17562872211018006
|View full text |Cite
|
Sign up to set email alerts
|

Trends of incidence and prognosis of primary adenocarcinoma of the bladder

Abstract: Background: Primary adenocarcinoma of the bladder (ACB) is a rare malignant tumor of the bladder with limited understanding of its incidence and prognosis. Methods: Patients diagnosed with ACB between 2004 and 2015 were obtained from the SEER database. The incidence changes of ACB patients between 1975 and 2016 were detected by Joinpoint software. Nomograms were constructed based on the results of multivariate Cox regression analysis to predict overall survival (OS) and cancer-specific survival (CSS) in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Our model contained the following variables produced from clinical practice: age at diagnosis, marital status at diagnosis, sex, primary site-labeled, grade, ICD-O-3 hist/behav, derived AJCC stage group 7th ed (2010–2015), derived AJCC T 7th ed (2010–2015), RX Summ-surg prim site (1998+), chemotherapy recode (yes, no/unk), CS tumor size (2004–2015), the total number of in situ/malignant tumors for patients, in which age was a significant risk variable for the bladder cancer-specific mortality, suggesting that the risk of death in bladder cancer patients would increase significantly with age. Prognostic analyses for bladder cancer conducted by other studies also showed that age played a crucial role in cancer death, and the death rate in patients increased with the increase of age at diagnosis [ 23 , 24 ]. Another risk factor appeared to be sex.…”
Section: Discussionmentioning
confidence: 99%
“…Our model contained the following variables produced from clinical practice: age at diagnosis, marital status at diagnosis, sex, primary site-labeled, grade, ICD-O-3 hist/behav, derived AJCC stage group 7th ed (2010–2015), derived AJCC T 7th ed (2010–2015), RX Summ-surg prim site (1998+), chemotherapy recode (yes, no/unk), CS tumor size (2004–2015), the total number of in situ/malignant tumors for patients, in which age was a significant risk variable for the bladder cancer-specific mortality, suggesting that the risk of death in bladder cancer patients would increase significantly with age. Prognostic analyses for bladder cancer conducted by other studies also showed that age played a crucial role in cancer death, and the death rate in patients increased with the increase of age at diagnosis [ 23 , 24 ]. Another risk factor appeared to be sex.…”
Section: Discussionmentioning
confidence: 99%
“…Zaghloul et al 117 showed significantly different distant metastasis-free rates among the three adenocarcinoma grades, although it had no significant effect on survival. Several recent studies on bladder adenocarcinomas (including urachal adenocarcinoma) from the SEER database showed grade (with varied cutoffs) to be an independent predictor of outcome 118–121 …”
Section: Grading Of Pure Non-urothelial Carcinomasmentioning
confidence: 99%
“…Several recent studies on bladder adenocarcinomas (including urachal adenocarcinoma) from the SEER database showed grade (with varied cutoffs) to be an independent predictor of outcome. [118][119][120][121] Proposal and Voting…”
Section: Grading Of Adenocarcinomamentioning
confidence: 99%